Product Liability, Defective Goods, and Consumer Compensation in Business Law - Marsal, Antonino Pedro; Darmawan, Didit; Hardyansah, Rommy (Metromedia, 2025)
This study discusses product liability in Indonesian business law, analysed through qualitative literature review. The legal framework is based on a combination of the Consumer Protection Law, the Civil Code, and various sectoral regulations such as those in the fields of health, food, and the environment. In this system, product defects including design, manufacturing, and information defects form the basis of a business's obligation to provide compensation in the form of refunds, replacement of goods or services, health care, or damages, with liability remaining even if the fault lies with another party in the distribution chain. While the Consumer Protection Law and the Civil Code provide the basis for lawsuits, sectoral regulations reinforce obligations in high-risk areas, supported by technical standards such as SNI and waste management regulations. Dispute resolution can be carried out directly, through the BPSK, or in court, including class action lawsuits. The effectiveness of this regime is highly dependent on the clarity of the definition of product defects, the integration of legal regulations, and the accessibility of compensation channels. Therefore, the study recommends strengthening the guidelines for evidence, increasing the capacity of dispute resolution institutions, and developing corporate risk management policies that are oriented towards product safety and consumer loss recovery.